Implementation and Analysis Audio Steganography Used Parity Coding for Symmetric Cryptography Key Delivery - Firdaus, Afany Zeinata; Yuliana, Mike; Samsono Hadi, Mochamman Zen (EMITTER International Journal of Engineering Technology, 2013)
In todays era of communication, online data transactions is increasing. Various information even more accessible, both upload and download. Because it takes a capable security system. Blowfish cryptographic equipped with Audio Steganography is one way to secure the data so that the data can not be accessed by unauthorized parties. In this study Audio Steganography technique is implemented using parity coding method that is used to send the key cryptography blowfish in e-commerce applications based on Android. The results obtained for the average computation time on stage insertion (embedding) the secret message is shorter than the average computation time making phase (extracting) the secret message. From the test results can also be seen that the more the number of characters pasted the greater the noise received, where the highest SNR is obtained when a character is inserted as many as 506 characters is equal to 11.9905 dB, while the lowest SNR obtained when a character is inserted as many as 2006 characters at 5,6897 dB .Keywords: audio steganograph, parity coding, embedding, extractin, cryptography blowfih.